A COURSE IN HERMENEUTICS OF WORKS OF ART IN HIGHER PROFESSIONAL EDUCATION PROGRAMMES - Bragina, Natalia; Jermolajeva, Jelena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The article stems from the problem that has developed in modern higher education programmes such as Humanities, History of Art and Musicology. Learners of these programmes are required to digest an increasingly large amount of information. Yet, the abundance in information, which is not always comparable in quality, obstructs the development of students’ analytical skills. It seems feasible to introduce an innovative course in Hermeneutics of Works of Art into the Humanities, History of Art and Musicology programmes, the course is based on a universal method of artwork analysis elaborated by one of the authors of the article. The article aims to outline the main principles of this course, which is meant to help learners to understand the formation of semantics in various forms of art and to identify the ways of emotional and intellectual impact of artworks. This objective can be achieved by drawing upon a limited number of artworks. The musicological method of analysis is taken as a basis since its technology has been elaborated most thoroughly. This method focuses on the analysis of the formal structure of the work because the form itself contains the most important information about the content. The article shows that the basic structures of European academic music, such as periods, two- and three-part forms, variations, and the sonata form, are universal and derive from the most ancient mythological prototypes. These structures can be easily found in all forms of art and have similar semantic connotations. The proposed method also includes the analysis of polyphony, motivational dramaturgy, and space-time relations in the text, as well as the psychoanalytic approach to content interpretation. The idea of the hermeneutic circle is used to harmonize a general analysis of an artwork and a detailed analysis of its separate elements. The approbation of the proposed study course has demonstrated good results in developing students’ abilities to analyse a work of art.